2011
DOI: 10.1039/c0cp01702g
|View full text |Cite
|
Sign up to set email alerts
|

On the proton conductivity in pure and gadolinium doped nanocrystalline cerium oxide

Abstract: Conductivity measurements were performed on microcrystalline and nanocrystalline ceria (undoped and doped) in dry as well as wet atmosphere. Below 200-250 °C, the nanocrystalline samples exhibit an enhanced total conductivity under wet conditions, which increases with decreasing temperature. In addition, thermo-gravimetric analysis revealed a strong water uptake below 200 °C. DC-polarization measurements confirm the ionic character of conductivity in the nanocrystalline samples at low temperatures. The role of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

20
108
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(128 citation statements)
references
References 13 publications
20
108
0
Order By: Relevance
“…At this stage it is important to reconsider the treatment of the grain boundary core as transparent with respect to charge transport and the overall applicability of the space-charge model to the system under consideration here. From eqn (11) it is evident that the space-charge layer thickness decreases with dopant concentration and may even approach the thickness of the grain boundary core. In the present case, using eqn (8) and the measured mean grain size of 0.36 mm, we compute a grain boundary width (2l sc ) of 1.2 nm (250 1C, dry air).…”
Section: Analysis and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…At this stage it is important to reconsider the treatment of the grain boundary core as transparent with respect to charge transport and the overall applicability of the space-charge model to the system under consideration here. From eqn (11) it is evident that the space-charge layer thickness decreases with dopant concentration and may even approach the thickness of the grain boundary core. In the present case, using eqn (8) and the measured mean grain size of 0.36 mm, we compute a grain boundary width (2l sc ) of 1.2 nm (250 1C, dry air).…”
Section: Analysis and Discussionmentioning
confidence: 99%
“…The assumption that the core is moreover ion-reversible is specifically motivated here by the observed increase in the grain boundary resistance upon humidification and invariance upon isotopic exchange, behaviors not expected for transport limited by the core itself. The validity of the assumption can furthermore be evaluated from a comparison of the grain boundary width implied directly from the impedance spectra according to eqn (8) and that implied from a solution to eqn (11). Although these two values cannot be computed entirely independently, agreement between the two terms is a necessary requirement for validation of the space-charge model in conjunction with an ion-reversible core.…”
Section: Analysis and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6b, the overall dependence of the conductivity on temperature, first decreasing then increasing with increasing temperature, with an inflection point at B400 1C, and on pH 2 O, is consistent with the identification of protons as the dominant mobile species at low temperature, and is in good agreement with typical behavior reported in the literature. 6 Remarkably, the non-monotonic dependence of conductivity on temperature holds true even under nominally dry oxygen, at which proton sorption onto or incorporation into the oxide must be extremely limited. At higher temperatures oxygen ion conduction presumably dominates the transport process, as indicated by the observation of increasing conductivity with increasing temperature and a decreasing impact of water partial pressure.…”
Section: Electrical Characterizationmentioning
confidence: 99%
“…However, no obvious protonic conductivity was observed. In contrast, researchers found that there is an enhanced protonic conductivity when the testing temperature is lower than 150 ℃ (27)(28)(29)(30)(31)(32)(33)(34). In order to investigate the potential protonic conductivity and the relative applications of hafnia-based compounds, the compound Hf 0.69 Y 0.31 O 2-δ (YSH) was synthesized in this study.…”
Section: Introductionmentioning
confidence: 99%